Heterosis and combining ability for quantitative traits in Canola (Brassica napus L.) using half diallel mating design - Simranpreet Kaur; Ravindra Kumar; Meenakshi Sharma; Vijay Singh; Saurabh Gupta (Journal of Oilseed Brassica, 2026)
In the year 2021-22, a set of 5 × 5 diallel crosses of canola were analyzed with their parents, to estimate heterosis as wellas general combining ability (GCA) and specific combining ability (SCA). Observations on numerous quantitativecharacters were recorded. Almost all of the variables showed significant differences in GCA and SCA. The presence ofboth additive and non-additive gene interactions for the inheritance of distinct traits was revealed by the large magnitudeof GCA and SCA effects. Parent IC-338967 was shown to be an excellent general combiner for seed yield, whereas BM 91was shown to be a good earliness combiner. In the desirable direction, the high-ranking specific crosses for yield and itscomponent were BM91 × EC338973, BM 91 × EC338976, BM9 1 × EC338977, EC338973 × EC338976, EC338973 × EC338967and EC338977 × EC338967. Heterosis was observed in the F1 generation, and it differed by character. Most of the traitsshowed significant positive nature of heterosis when compared to a better parent and commercial check. For yield andassociated parameters, all of the hybrids had a significant amount of heterobeltiosis. As a result, it might be furtheranalyzed for detailed heterosis assessment or even in a breeding program to find the best cultivar/s.